(untitled) (Anwer Khan Modern Medical College Journal, 2012)
Pedicled flaps play an important role in cancer treatment centers, particularly in developing and emerging countries. Although different flaps can be used for facial reconstruction but Pectoralis major myocutaneous flap is still considered the workhorse for maxillofacial reconstruction because of simple procedure and high success rate, while other flaps of facial region ranging from pedicled to free flaps require greater surgical skills along with unpredictable results.The aim of this study is to find outcomes of Pectoralis major myocutaneous flap in reconstruction of middle and lower facial regions. Main outcome measures are vitality of the Pectoralis major myocutaneous flap, donor site morbidity and recipient and donor site complications. This study was carried out on 36 patients in BSMMU and Health & Hope Hospital in Dhaka from 1st April 2005 to 30th June 2011 who require soft tissue reconstruction of defects of middle and lower facial regions. The age and sex of the patients and size of defect were analyzed. Vitality of Pectoralis major myocutaneous flap, donor site morbidity and donor and recipient site complications were studied. In this study, male female ratio was 13:5; mean age 50 the success rate of was 100%. All of the flaps were vital but 13.8% of the flaps had partial loss of flap. Pectoralis major myocutaneous flap is a versatile flap as it can not only provide skin and mucosal cover simultaneously, but also provide adequate muscle bulk for through and through defects. It doesn’t cause any hindrance in mandibular movements. DOI: http://dx.doi.org/10.3329/akmmcj.v3i2.11690 AKMMC J 2012: 3(2): 23-29